Improving asthma care with Asthma-COPD Afterhours Respiratory Nurse at Emergency (A-CARE) - Mariko Siyue Koh; Si Yuan Chew; Jenneth Yue Ling Leow; Adrian Kok Wai Chan; Jing Jing Chan; Kenneth Boon Kiat Tan; Butta Aman; Donna Tan (BMJ Open Quality, 2020)
Background Emergency departments (ED) are important providers of asthma care, particularly after-hours. We identified gaps for quality improvement such as suboptimal adherence rates to three key recommendations from the Global Initiative for Asthma (GINA) guidelines for discharge management asthma guidelines. These were: the prescription of oral and inhaled corticosteroids (OCS and ICS) and issuance of outpatient follow-up for patients discharged from the ED.Aim To achieve an adherence rate of 80% to GINA guidelines for ED discharge management by providing after-hours asthma counselling services.Methods We implemented Asthma-COPD Afterhours Respiratory Nurse at Emergency (A-CARE) according to the Plan-Do-Study-Act (PDSA) framework to provide after-hours asthma counselling and clinical decision support to ED physicians three nights a week. Data on adherence rates to the GINA guidelines were collected and analysed on a run chart.Results After 17 months’ follow-up, a sustained improvement was observed in patients reviewed by A-CARE in the median adherence rates to OCS prescription (58% vs 86%), ICS initiation (27% vs 67%) and issuance of follow-up (69% vs 92%), respectively. The overall impact was, however, limited by a suboptimal referral rate to A-CARE (16%) in a clinical audit of all ED patients with asthma. Nonetheless, in this audit, attendance rates for patients referred to our respiratory department for follow-up were higher in those receiving asthma counselling compared with those who did not (41.7% vs 15.9%, p=0.0388).Conclusion Sustained improvements in the adherence rates to guidelines were achieved for patients reviewed by A-CARE but were limited in overall impact due to suboptimal referral rate. We plan to improve the quality of asthma care by implementing further PDSA cycles to increase the referral rates to A-CARE.